Biomass-based electrospinning composite nanofiber membrane for formaldehyde adsorption as well as preparation method and application of biomass-based electrospinning composite nanofiber membrane

By introducing -OH and -NH2 groups and citric acid into cellulose and chitosan, the biomass-based electrospinning composite nanofiber membrane is constructed by electrospinning method, which solves the high cost and efficiency of formaldehyde adsorption in the prior art. The problem of low results in efficient and environmentally friendly formaldehyde adsorption effect.

CN119158545APending Publication Date: 2024-12-20SOUTHWEST FORESTRY UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411377707.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The prior art has problems in the adsorption of formaldehyde, low production efficiency, difficult to regulate nanofiber morphology and limited use scenarios, and the materials used are not renewable and the process is complicated.

Method used

The biomass-based electrospinning composite nanofiber membrane was constructed by electrospinning. By introducing -OH and -NH2 groups and oxygen-containing functional groups into cellulose and chitosan, the structural stability of the nanofiber membrane was improved. and the physicochemical adsorption properties of gaseous formaldehyde.

Benefits of technology

It realizes a nanofiber membrane with low air resistance and high porosity, improves formaldehyde adsorption efficiency, and is simple in process, low in cost and environmentally friendly, and is suitable for formaldehyde adsorbents.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158545A_ABST
    Figure CN119158545A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adsorbent materials, and particularly discloses a biomass-based electrospinning composite nanofiber membrane for formaldehyde adsorption as well as a preparation method and application of the biomass-based electrospinning composite nanofiber membrane. Cellulose and chitosan serve as raw materials, natural cellulose contains a large number of hydroxyl groups, chitosan contains a large number of amino groups, meanwhile, carboxyl containing oxygen-containing functional groups and hydroxyl citric acid are introduced into a composite system, and the nanofiber membrane with the formaldehyde adsorption function is constructed through an electrostatic spinning method. Due to the existence of-OH and-NH2 groups, on one hand, the structural stability between nodes of the nanofiber membrane is improved, so that the nanofiber membrane with the low air resistance characteristic and the high porosity is obtained, and meanwhile, due to the existence of several oxygen-containing and nitrogen-containing functional groups, the physical and chemical adsorption characteristic of the nanofiber membrane to gaseous formaldehyde molecules is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adsorbent materials, and in particular relates to a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption, and a preparation method and application thereof. Background Art

[0002] With the development of economy and the improvement of people's living standards, building decoration materials made of various raw materials have entered families, and the chemical formaldehyde is recognized as the most representative of indoor air pollution. Formaldehyde is a highly toxic substance. It ranks second on the priority control list of toxic chemicals in my country. Formaldehyde has been identified by the World Health Organization as a carcinogen and teratogen, and is one of the potential strong mutagens. Long-term exposure to an environment with excessive formaldehyde can easily cause discomfort such as throat and nasal pain, headache, nausea, cough, and breathing problems. Even worse, it can cause liver and kidney failure, chromosome mutations, etc. Formaldehyde has strong carcinogenic and cancer-promoting effects. A large number of documents record that the impact of formaldehyde on human health is mainly manifested in abnormal smell, irritation, allergies, abnormal lung function, abnormal liver function, and abnormal immune function. Therefore, the efficient and low-cost removal of formaldehyde in the environment has become an urgent problem to be solved. According to relevant data from the World Health Organization, indoor air pollution causes 4.3 million deaths worldwide each year.

[0003] Common processes in the prior art, such as the technical solution disclosed in the invention patent application with publication number CN110106579A and titled “An antibacterial fiber containing MOF and preparation method thereof”: Zn@MOF nanomaterials are mixed with a concentrated solution of antibacterial components prepared from traditional Chinese medicine powder, and dried to obtain an antibacterial material; the fibers and antibacterial materials are dissolved in a chitosan solution, and the antibacterial fibers containing MOF are obtained after electrospinning and freeze-drying. However, the morphology of nanofibers prepared by electrospinning technology is difficult to control, and the production efficiency is not high. The antibacterial fibers after freeze-drying are relatively brittle. This technical solution cannot solve the problems of preparation cost and production efficiency, and the use scenarios of the obtained products are relatively limited. Another example is the announcement number CN111013271B, titled “A nanofiber-loaded metal organic framework air purification material and preparation method thereof”. A polystyrene (PS) / cobalt acetate (Co(AC)2) nanofiber membrane was prepared by electrospinning, and then Co was soaked. 2+ The 2-methylimidazole ligand in the immersion solution is coordinated to make the cobalt-based metal organic framework (ZIF-67) material grow in situ on the nanofibers. The PS and cobalt acetate raw materials used in this method are expensive and non-renewable, and the process is complicated. The prepared nanofiber membrane has a general adsorption efficiency for formaldehyde. Summary of the invention

[0004] The purpose of the present invention is to address the above-mentioned deficiencies in the prior art and provide a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption, a preparation method and application thereof. A formaldehyde adsorption functional nanofiber membrane is constructed by electrospinning. The presence of -OH and -NH2 groups is beneficial to improving the structural stability between the nodes of the nanofiber membrane, thereby obtaining a nanofiber membrane with low air resistance characteristics and high porosity. At the same time, the presence of several oxygen-containing and nitrogen-containing functional groups effectively improves the physicochemical adsorption characteristics of the nanofiber membrane for gaseous formaldehyde molecules.

[0005] To achieve the above object, the present invention adopts the following technical solution: The first object of the present invention is to provide a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption, which is characterized by comprising the following specific steps: S1, dissolving citric acid in N, N-2-methylformamide to obtain a first solution, dissolving chitosan in 1-ethyl-3-methylimidazolium acetate to obtain a second solution, dissolving microcrystalline cellulose in 1-ethyl-3-methylimidazolium acetate to obtain a third solution, and dissolving polyacrylonitrile in N, N-2-methylformamide (DMF) to obtain a fourth solution; S2, mixing the mixed solution of the first solution, the second solution and the third solution with the fourth solution in a certain proportion, stirring evenly, and standing for 8 to 14 hours to obtain a spinning solution; S3, taking the spinning solution obtained in step S2 and passing it through an electrospinning device to obtain a biomass-based electrospun composite nanofiber membrane.

[0006] Furthermore, in step S1, the mass concentration of citric acid in the first solution is 0.5% to 10%, the mass concentration of chitosan in the second solution is 3% to 4%, the mass concentration of microcrystalline cellulose in the third solution is 5% to 6%, and the mass concentration of polyacrylonitrile in the fourth solution is 12% to 13%.

[0007] Furthermore, in step S1, the mass concentration of citric acid in the first solution is 4% to 6%.

[0008] Furthermore, in step S2, the volume ratio of the first solution, the second solution and the third solution is 1:1:1~4:1:1.

[0009] Furthermore, in step S2, the molar ratio of the mixed solution to the fourth solution is 2:8 to 5:5.

[0010] Furthermore, in step S2, stirring is performed at 20-30° C. and 100-200 r / min for 1-2 h.

[0011] Furthermore, the electrospinning process is as follows: the solution flow rate is adjusted to 0.5-1.5 mL / h, the acceleration voltage is 14-18 kV, and the distance between the needle and the collector is 10-20 cm.

[0012] The second object of the present invention is to provide a biomass-based electrospun composite nanofiber membrane prepared by the above-mentioned preparation method.

[0013] The third object of the present invention is to provide the use of the above-mentioned biomass-based electrospun composite nanofiber membrane in the preparation of adsorbent products.

[0014] A fourth object of the present invention is to provide a formaldehyde adsorbent comprising the biomass-based electrospun composite nanofiber membrane as described in claim 8.

[0015] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects: (1) The biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption provided by the present invention uses cellulose and chitosan as raw materials. Natural cellulose contains a large amount of hydroxyl (-OH) groups, and chitosan itself contains a large amount of amino (-NH2) groups. At the same time, carboxyl (-COOH) and hydroxyl (-OH) citric acid containing oxygen-containing functional groups are introduced into the composite system, and a formaldehyde adsorption functional nanofiber membrane is constructed by electrospinning. The presence of -OH and -NH2 groups is beneficial to improving the structural stability between the nodes of the nanofiber membrane, thereby obtaining a nanofiber membrane with low air resistance characteristics and high porosity. At the same time, the presence of several oxygen-containing and nitrogen-containing functional groups effectively improves the physical and chemical adsorption characteristics of the nanofiber membrane for gaseous formaldehyde molecules.

[0016] (2) The preparation method provided by the present invention has the advantages of simple process, easy control, green and environmentally friendly, and relatively low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of the biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption provided by the present invention; Figure 2 This is a nanoindentation modulus diagram of the biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption provided by the present invention. DETAILED DESCRIPTION

[0018] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.

[0019] Example 1 S1. Weigh 0.025g of CA and add it to a reagent bottle for later use. Then measure 5.025g of N, N-2-methylformamide and pour it into the reagent bottle. Control a certain speed at room temperature and stir until CA is completely dissolved to prepare a 0.5wt% CA solution to obtain the first solution. Weigh 0.24g of CS and add it to a reagent bottle for later use. Then measure 7.76g of 1-ethyl-3-methylimidazolium acetate and pour it into the reagent bottle. Put the reagent bottle into an oil bath pot, control the temperature to 80°C, control a certain speed, stir until CS is completely dissolved to prepare a 3.0wt% CS solution to obtain the second solution. Weigh 0.4g of microcrystals. Pour cellulose (MCC) into a reagent bottle for later use, measure 7.6g of 1-ethyl-3-methylimidazolium acetate, pour it into the reagent bottle, put the reagent bottle into an oil bath, control the temperature to 80°C, control a certain speed, stir until MCC is completely dissolved, prepare a 5.0wt% MCC solution, and obtain a third solution. Weigh 1.08g of PAN, measure 7.92g of N, N-2-methylformamide solution, pour it into the reagent bottle, put the reagent bottle into an oil bath, control the temperature to 80°C, control a certain speed, stir until PAN is completely dissolved, prepare a 12.0wt% PAN solution, and obtain a fourth solution. S2, mixing the mixed solution of the first solution, the second solution and the third solution with the fourth solution in a certain proportion, stirring evenly, and standing for 8 to 14 hours to obtain a spinning solution; S3, taking the spinning solution obtained in step S2 and passing it through an electrospinning device to obtain a biomass-based electrospun composite nanofiber membrane.

[0020] In step S2, the volume ratio of the first solution, the second solution and the third solution is 1:1:1-4:1:1; the molar ratio of the mixed solution of the first solution, the second solution and the third solution to the fourth solution is 2:8-5:5.

[0021] In step S3, the solution flow rate is adjusted to 0.5-1.5 mL / h, the acceleration voltage is 14-18 kV, and the needle-collector distance is 10-20 cm.

[0022] The prepared biomass-based electrospun composite nanofiber membrane was used in the formaldehyde adsorption test to evaluate its adsorption performance. The flow meter was set to 200m 3 / h, measure a set of data at intervals of 10 minutes. Each time, ventilate the gas collecting bottle to be tested for 60 seconds, dilute it to a 100ml volumetric flask, transfer 2ml to a colorimetric tube with a pipette, dilute the colorimetric tube to 10ml with distilled water, add 2ml of color developer and shake well, heat for 10 minutes, and after protecting from light for 1h, use an ultraviolet spectrophotometer to determine the concentration of the formaldehyde solution after adsorption. The adsorption results measured in this example are shown in Table 1.

[0023] q=(t-integral area)*0.2*C0 / m Wherein, q is the adsorption amount, unit is mg / g; the integral area is obtained by taking time as the horizontal coordinate and C0 / Ct as the vertical coordinate; C0 is the initial concentration of formaldehyde, Ct is the concentration after adsorption at time t; m is the mass of the nanofiber membrane used for adsorption, g.

[0024] Example 2 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 1%.

[0025] Example 3 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 2%.

[0026] Example 4 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 3%.

[0027] Example 5 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 4%.

[0028] Example 6 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 6%.

[0029] Example 7 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 8%.

[0030] Example 8 This embodiment provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with that of Example 1, except that the concentration of the citric acid solution is 10%.

[0031] Comparative Example 1 This comparative example provides a method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption. The basic method is consistent with Example 1, except that the concentration of the citric acid solution is 0%.

[0032] Formaldehyde adsorption tests were carried out on Examples 1-8 and Comparative Example 1, and the results are shown in Table 1.

[0033] Table 1. Formaldehyde adsorption test results.

[0034]

[0035] The citric acid biomass-based electrospun nanofiber membrane adsorption material prepared by the present invention can give full play to the adsorption advantage of citric acid carboxyl groups and has a high adsorption efficiency for gaseous formaldehyde. Moreover, according to experiments, when the citric acid concentration is 4%, the adsorption efficiency of the composite nanofiber membrane is the highest, reaching 209.93 mg / g.

[0036] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.

[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a biomass-based electrospun composite nanofiber membrane for formaldehyde adsorption, characterized in that: The specific steps include: S1, dissolving citric acid in N, N-2-methylformamide to obtain a first solution, dissolving chitosan in 1-ethyl-3-methylimidazolium acetate to obtain a second solution, dissolving microcrystalline cellulose in 1-ethyl-3-methylimidazolium acetate to obtain a third solution, and dissolving polyacrylonitrile in N, N-2-methylformamide (DMF) to obtain a fourth solution; S2, mixing the mixed solution of the first solution, the second solution and the third solution with the fourth solution in a certain proportion, stirring evenly, and standing for 8 to 14 hours to obtain a spinning solution; S3, taking the spinning solution obtained in step S2 and passing it through an electrospinning device to obtain a biomass-based electrospun composite nanofiber membrane.

2. The preparation method according to claim 1, characterized in that In step S1, the mass concentration of citric acid in the first solution is 0.5%-10%, the mass concentration of chitosan in the second solution is 3%-4%, the mass concentration of microcrystalline cellulose in the third solution is 5%-6%, and the mass concentration of polyacrylonitrile in the fourth solution is 12%-13%.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass concentration of citric acid in the first solution is 4% to 6%.

4. The preparation method according to claim 1, characterized in that: In step S2, the volume ratio of the first solution, the second solution and the third solution is 1:1:1~4:1:

1.

5. The preparation method according to claim 4, characterized in that: In step S2, the molar ratio of the mixed solution to the fourth solution is 2:8 to 5:

5.

6. The preparation method according to claim 1, characterized in that: In step S2, stirring is carried out at 20-30° C. and 100-200 r / min for 1-2 h.

7. The preparation method according to claim 1, characterized in that In step S3, the electrospinning process is as follows: the solution flow rate is adjusted to 0.5-1.5 mL / h, the acceleration voltage is 14-18 kV, and the distance between the needle and the collector is 10-20 cm.

8. A biomass-based electrospun composite nanofiber membrane, characterized in that: The preparation is obtained by the preparation method as described in claims 1-7.

9. Use of the biomass-based electrospun composite nanofiber membrane as claimed in claim 8 in the preparation of adsorbent products.

10. A formaldehyde adsorbent, characterized in that: It comprises the biomass-based electrospun composite nanofiber membrane as described in claim 8.

Citation Information

Patent Citations

  • MOF-containing antibacterial fiber and preparing method thereof

    CN110106579A

  • A nanofiber-supported metal-organic framework air purification material and its preparation method

    CN111013271B